Past President's Message - Mininder S. Kocher (Journal of the Pediatric Orthopaedic Society of North America, 2023)
The 2022 POSNA Annual Meeting Pre-Course was the last single topic pre-course for POSNA. Going forward, the Annual Meeting will commence in the morning with a full academic agenda, including scientific talks and symposia. For the last pre-course, I wanted to choose a topic that was of vital importance to POSNA and required a deeper dive: Diversity, Equity, and Inclusion. I commend our pre-course chair, Dr. Julie Samora, on developing and executing an extraordinary program. Diversity issues are a hot topic; however, they remain difficult to discuss openly and are challenging to develop actionable strategies. The title of the pre-course was “Improving Patient Care through Diversity, Equity, and Inclusion.” This was intentional. The mission of POSNA is to “Advance Pediatric Orthopaedics by Promoting Education, Research, and Quality Care.” Diverse organizations make better decisions and outperform nondiverse organizations. Culturally appropriate healthcare that appreciates diversity is ultimately better for patients and results in better patient outcomes. Thus, diversity is not just politically correct, it is essential for our profession and our patients. As a subspecialty, Pediatric Orthopaedics leads the overall profession of Orthopaedic Surgery in terms of diversity. Approximately 25% of POSNA active members are female, and approximately 40% of candidate members are female. However, this is like having the fastest time in the slowest heat. Orthopaedic Surgery has the least diversity in terms of sex and race of all medical professions. Approximately 7% of AAOS members are female. Women account for 14.5% of orthopaedic residents; however, only 3.5% of orthopaedic residents are Hispanic/Latino and only 5.4% are African-American. This is unacceptable. What can POSNA do? POSNA must continue to lead in terms of greater diversity, equity, and inclusion within Pediatric Orthopaedics and orthopaedics at large. POSNA established a diversity task force that has been formalized into the Justice, Equity, Diversity, and Inclusion (JEDI) standing committee within the President’s Council. The Board of Directors has established a restricted fund to support DEI initiatives, including research grants specific to diverse investigators within pediatric orthopaedics. POSNA continues to work with organizations such as Nth Dimensions, the Ruth Jackson Society, the J. Robert Gladden Society, and AAOS to grow the pipeline of females and underrepresented minorities within Orthopaedic Surgery. At the 2022 Annual Meeting and IPOS®, POSNA supported Pride Ortho, which hosted an amazing reception for LGBTQ+ members and their allies. But POSNA must do more. As the first Asian-American President of POSNA, I appreciate what it is like to be the other; however, we cannot fully understand each other’s unique experiences. The POSNA Board of Directors includes 30% women and 30% non-white members. We need more women and underrepresented minorities in positions of leadership in the society. POSNA early-career and mid-career leadership development programs can help identify and develop our future leaders. We need to appreciate how unconscious bias can affect our interactions with each other and with our patients and families. Most importantly, we need to keep diversity issues at the forefront and in our conversations. We need to appreciate and support diverse views and perspectives. Ultimately, this will be better for our organization and for our patients. After all, that is our mission.